Effect of Petroleum Products on Steel Fiber Reinforced Concrete (Journal of Engineering, 2013)
This Investigation aims to study the effect of adding Steel fibers with different volume fractions Vf (o.5, 0.75, and 1% by volume of concrete) with aspect ratio 100 on mechanical properties of concrete, and alsofinding the influence of petroleum products (Kerosene and Diesel) on mechanical properties of Steel Fiber Reinforced Concrete (SFRC).The experimental work consists of two groups: group one consists of specimens (cubes and prisms) plain and concrete reinforced with steel fiber exposed to continuous curing with water. Group two consists ofspecimens (cubes and prisms) plain and concrete reinforced with steel fiber exposed to kerosene and diesel after curing them in water for 28 days before exposure. The results of all tests refer that the specimens (plain and reinforced concrete with steel fiber with different volume fraction) exposed to kerosene were better than the specimens (plain and reinforced concrete with steel fiber with different volume fraction) exposed to diesel.